Transatlantic Catholicism: Rethinking the Nature of the Catholic Tradition in the Early Modern Period - Armstrong, Megan C. (History compass, 2007)
Recent scholarship makes a case for examining the Atlantic world as a Catholic space throughout the Early Modern period. The Catholic Church was the most expansive and broadly flung of the different religious institutions in the West throughout the Early Modern period. For better or worse, the Catholic spiritual tradition was also a critical force in shaping cultures on both sides of the ocean, and it was also itself informed by the many cultures it encountered. While historians on both sides of the Atlantic remain region-centric in their focus, this article will suggest that a comparative examination of the Catholic tradition in a broader cultural context will best shed light on the resiliency of this tradition in an age of spiritual upheaval.